Digital boundaries: A study into how mobile devices and information + communication technologies can influence the social programming, spatial conditions and construction of public architecture - Van 'T Hof, Marcus Daniel (School of Architecture, Planning and Geomatics, 2018)
DIGITAL BOUNDARIES explores the notion of how ICTs and mobile devices can influence the social programming, spatial conditions and construction of public architecture. This topic is derived from the study of Urban Informatics which looks at three key actors: people, place and technology. This can be seen in South Africa where many young individuals inhabit public buildings in the urban environment purely to be connected to wireless internet through their mobile devices. This is done so that they are able to do research for studies, look for job opportunities or socialise. This digital infrastructure then becomes an important aspect of the public realm, not only for personal benefit and need, but for attracting people to place. Situated in the Nyanga Junction precinct south of Gugulethu, the architectural proposition looks at adding digital infrastructure to this complex precinct in the informal area of Cape Town through three scales of architecture; small, medium and large. The small scale is that of Wi-Fi hotspots at street level embedded within the informal market at ten strategically located sites. The medium scale interventions are upgrades to four existing trade posts elevated above at first floor level. Lastly the large scale which is of catalytic and institutional architecture at two proposed sites, of which one is the main architectural focus of the design dissertation and explored further. The architectural programme provides spaces for: IT learning and skills development to help individuals seek employment, collaborative hubs for those developing new entrepreneurial ideas, and youth hubs for students to study and socialise. These three scales and their locality have been informed by social thresholds developed through the theory and technology studies that have been influential in the urban strategy of the design dissertation. It has created a framework for digital infrastructure to be implemented that will help enhance the public realm for a safer and more conducive urban environment.